Comparative health systems : a new framework - Toth, Federico (Cambridge : Cambridge University Press, 2021)
The standard classifications of health systems don't allow for the complexity and variety that exists around the world. Federico Toth sets out a new framework for understanding the many ways in which health systems can be organized and systematically analyses the health systems chosen by 27 OECD countries. He provides a great deal of up-to-date data on financing models, healthcare spending, insurance coverage, methods of organizing providers, healthcare personnel, remuneration methods for doctors and hospitals, development trajectories and recent reforms. For each of the major components of the healthcare system, the organizational models and the possible variants from which individual countries can ideally select are defined. Then, based on the organizational solutions actually adopted, the various national systems are grouped into homogeneous families. With its clear, jargon-free language and concrete examples, this is the most accessible comparative study of international healthcare arrangements available.
Seven Financing Models -- Funding Healthcare : Variants and Hybrid Systems -- Healthcare Expenditure and Insurance Coverage -- Healthcare Provision : Integrated vs. Separated Systems -- Financing Provision : Four families and a Few Outliers -- Hospitals, Doctors and Nurses -- Healthcare Reforms over the Last 30 Years -- Health Politics.
Title from publisher's bibliographic system (viewed on 20 Aug 2021).
Keywords: Hospitals -- Business management